A maternity case with human remains from a XIII–XIV century burial at Uceda, Guadalajara, Central Spain. (December 2015) - Gomes, C.; Palomo-Díez, S.; Dorado-Fernandéz, E.; Ruiz-Mediavilla, E.; Magaña-Loarte, C.; Ramírez-González, I.; López-Parra, A.M.; Baeza-Richer, C.; Gibaja, J.; Arroyo-Pardo, E.
Abstract: In a High Medieval age cemetery, dated from the XIII-XIV century (Uceda, Guadalajara, Central Spain), two bodies were found, buried in a curious position. One of the bodies, an adult, had close to its abdominal area a small number of little bones. It was not clear if it could have been a pregnant woman or, otherwise, two separated burials, at different times. Anthropological experts confirmed that the second individual should be a fetus, being absolutely impossible to determine the sex. Furthermore, the adult was appointed as a woman. Concerning the condition of the samples, the adult one was preserved, obeying to the authenticity criteria to select evidences for a critical DNA analysis. But the samples belonging to the second individual were very delicate and fragile, complicating the sampling work. A genetic study will be carried out to find if there is any biological bond between the individuals, as well as, their biological sex. The analysis procedure had to be somewhat modified due to the sensitivity of the second individual samples. So far, our preliminary results reveal that, if both individuals are not linked by maternal kinship, they must be, at least, relatives by maternal side, since they share the same maternal lineage. Conclusions reached in the present study can help in mass disasters cases. In such situations, it is crucial to determine kinships between samples, despite their advanced state of degradation, which makes the improvement of this procedure a crucial point in forensic genetics.